GE_GERICHTE P/22688/2019 vom 12. Juli 2021 - GE Cour de justice (2021)
délit impossible de viol avec cruauté;contrainte sexuelle avec cruauté;IN DUBIO PRO REO | CP.190.al1; CP.190.al3; CP.22.al1; CP.189.al1; CP.189.al3